2021
DOI: 10.1177/09636897211048786
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Heart Function After Transplantation of Encapsulated Stem Cells Induced with miR-1/Myocd in Myocardial Infarction Model of Rat

Abstract: Cardiovascular disease is one of the most common causes of death worldwide. Mesenchymal stem cells (MSCs) are one of the most common sources in cell-based therapies in heart regeneration. There are several methods to differentiate MSCs into cardiac-like cells, such as gene induction. Moreover, using a three-dimensional (3D) culture, such as hydrogels increases efficiency of differentiation. In the current study, mouse adipose-derived MSCs were co-transduced with lentiviruses containing microRNA-1 ( miR-1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The chitosan-derived hydrogels encapsulate the stem cells and promote their maturation into the cardiomyocytes [ 107 ]. Chitosan, protein and stem cell hydrogels have been applied intramuscularly to promote the secretion of the growth factors that improve the myocardial conditions [ 108 ], as in the case of the expression of the vascular endothelial growth factor (VEGF), which allows for the revascularization in the infarcted area [ 109 ]. In addition, the porous and fibrous chitosan scaffolds are used as support structures to promote the stem cells’ maturation into the cardiomyocytes [ 110 ].…”
Section: Scaffolds For Cardiac Tissue Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…The chitosan-derived hydrogels encapsulate the stem cells and promote their maturation into the cardiomyocytes [ 107 ]. Chitosan, protein and stem cell hydrogels have been applied intramuscularly to promote the secretion of the growth factors that improve the myocardial conditions [ 108 ], as in the case of the expression of the vascular endothelial growth factor (VEGF), which allows for the revascularization in the infarcted area [ 109 ]. In addition, the porous and fibrous chitosan scaffolds are used as support structures to promote the stem cells’ maturation into the cardiomyocytes [ 110 ].…”
Section: Scaffolds For Cardiac Tissue Regenerationmentioning
confidence: 99%
“…For example, it has been shown that protein-containing hydrogels can promote cell growth and anchoring by promoting the maturation of the stem cells within the hydrogel [ 108 ]. However, the rapid biodegradability of the protein-containing hydrogels, such as gelatin hydrogels, limits the time required for progenitor cell maturation [ 108 , 131 ].…”
Section: Chitosanmentioning
confidence: 99%
See 1 more Smart Citation
“…This method of silencing the ACE gene could completely block the effect of ACE after myocardial infarction compared with lowering Ang II (Human angiotension Ⅱ) level with ACE inhibitor [ 190 ]. In addition, the induction of MSCs by microRNA and cardiomyocytes combined with hydrogel can improve the differentiation efficiency of MSCs into iCMs (induced cardiomyocyte-like cells) to improve the cardiac function of the MI model after transplantation [ 191 ]. In particular, miR-21-5p (microRNA-21-5p), which is highly expressed in endothelial cells, can stimulate angiogenesis by targeting anti-angiogenic genes [ 192 ].…”
Section: Hydrogels As Factor/protein Drug Gene Release Carriersmentioning
confidence: 99%
“…Unless appropriate interventions are implemented, the prevalence and mortality from cardiovascular diseases would increase further. 1 , 2 In recent years, the occurrence of CVD has been markedly younger, and the incidence and mortality of aging cardiovascular disease have also increased significantly. 3 Therefore, controlling cardiovascular disease-related risk factors is of major clinical significance and social value for the effective prevention and treatment of CVD.…”
Section: Introductionmentioning
confidence: 99%